Surgery for Metastasis to the Pancreas: Is it Safe and Effective?. Issue 8 (1st May 2013) - Niess, Hanno; Conrad, Claudius; Kleespies, Axel; Haas, Florian; Bao, Qi; Jauch, Karl‐Walter; Graeb, Christian; Bruns, Christiane J.
Abstract Background Pancreatic metastases are rare and only sparse data exists on treatment options. After recent advances in pancreatic surgery, metastasectomies have become promising treatment alternatives. Methods Twenty‐six patients underwent pancreatic metastasectomy between 1991 and 2010 at our institution. Data was evaluated retrospectively. Results Renal cell carcinoma was the most common origin of pancreatic metastases (n = 16; 62%). Other primaries include gall bladder carcinoma, leiomyosarcoma, colon cancer (all n = 2), and others. The median time interval between primary tumor and pancreatic resection was 5.3 years [0–24]. Eleven pancreatic head resections (42%), fourteen distal pancreatectomies (54%), and one total pancreatectomy were performed (4%). The estimated 3‐ and 5‐year survival rates were 73.2% and 52.3%, respectively. The estimated median overall survival was 63 months (CI: 37.8–88.1 months). There' was no perioperative death. The complication rate and relaparotomy rate was 31% and 19%, respectively. Patients suffering from synchronous metastases at the time of pancreatic surgery had a statistically significant shorter median overall survival time (11 months vs. 64 months). Conclusions Despite the operative risk involved, we believe that pancreatic resection should be considered in selected patients with good performance status, stable disease and isolated pancreatic metastases. J. Surg. Oncol. 2013;107:859–864. © 2013 Wiley Periodicals, Inc.